THE EFFECT OF DIVIDEND POLICY, MANAGERIAL OWNERSHIP AND PROFITABILITY ON COMPANY VALUE WITH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE AS MODERATING VARIABLES IN THE BANKING SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE 2017-2021 - Risa, Fitria; Fachrudin, Fachrudin; Satriawan, Bambang; Robin, Robin; Khaddafi, Muammar; Wibisono, Chablullah (CV. Radja Publika, 2022)
This study aims to analyze dividend policy, managerial ownership and profitability of firm value by disclosing Corporate Social Responsibility as a Moderating Variable in banking companies listed on the Indonesia Stock Exchange for the period 2017-2021. The population in this study were 46 banking companies. The sample selection method used purposive sampling technique, so the number of samples used was 17 banking companies. The number of observations used is 85 observations. The type of data used is secondary data with the data analysis technique used is panel data regression analysis with multiple linear regression test using Eviews software. The results show that dividend policy has a positive but not significant effect on firm value, Managerial Ownership has a positive but not significant effect on Firm Value, and Profitability has a positive but not significant effect on Firm Value. Corporate Social Responsibility is not able to moderate dividend habits on firm value, Corporate Social Responsibility is able to moderate managerial ownership on firm value, and Corporate Social Responsibility is able to moderate profitability to firm value.